Cross-cultural pragmatic failure - Peter McGee (Peoples' Friendship University of Russia (RUDN University), 2019)
This paper explores the study of failures in intercultural communication due to misunderstandings in the linguistic field of pragmatics. It focuses on three areas of pragmatics; compliments, refusals and complaints and examines how cultural misunderstandings can arise in these areas with examples from different communities. The paper emphasises that the study of pragmatics needs a stronger focus in the teaching and learning of languages in teaching materials, in classroom practice and especially in computer-mediated communication, particularly through social media. The researcher stresses that more research needs to take place into not only what pragmatic failures in communication occur and why they happen across cultures and language but also into how they can be repaired and mutual understanding restored.